2005
DOI: 10.1016/j.jacc.2005.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Gadolinium-Enhanced Cardiovascular Magnetic Resonance in the Diagnosis of Cardiac Sarcoidosis

Abstract: In patients with sarcoidosis, CMR is a useful diagnostic tool to determine cardiac involvement. New diagnostic guidelines should include CMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 498 publications
(123 citation statements)
references
References 28 publications
2
118
1
2
Order By: Relevance
“…In cardiac amyloidosis, accumulated abnormal proteins expand more widely in the interstitial space,10 resulting in several different patterns of LGE on CMR such as entire subendocardial circumference, focal intramural, and subepicardial patterns in both ventricles 211 On the other hand, it is well documented that LGE in CS is patchy and typically involves the basal septum and lateral LV walls, but rarely in the free wall of the RV 45 Yared et al 12.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac amyloidosis, accumulated abnormal proteins expand more widely in the interstitial space,10 resulting in several different patterns of LGE on CMR such as entire subendocardial circumference, focal intramural, and subepicardial patterns in both ventricles 211 On the other hand, it is well documented that LGE in CS is patchy and typically involves the basal septum and lateral LV walls, but rarely in the free wall of the RV 45 Yared et al 12.…”
Section: Discussionmentioning
confidence: 99%
“…There is a variable pattern of LGE seen with cardiac sarcoid with a classic pattern of midwall or epicardial LGE, but it can also present with subendocardial or transmural enhancement in almost any distribution. One study of CMR in 58 patients with biopsy proven pulmonary sarcoid found 19 patients with evidence of LGE, mostly in the basal and lateral myocardium, a higher prevalence than identified by standard Japanese Ministry of Health (JMH) guidelines (61). Another study of 81 patients with extracardiac sarcoidosis followed on average for 21 months demonstrated a 2-fold higher rate of cardiac involvement by CMR than by JMH guidelines (62).…”
Section: Nonischemic Cardiomyopathiesmentioning
confidence: 99%
“…Early enhancement of sarcoid granulomas in T2-weighted images suggests the presence of inflammation and edema, whereas DE indicates fibrotic changes and scarring [41, 42]. Commonly, the two phases overlap.…”
Section: Cardiac Mrimentioning
confidence: 99%
“…Commonly, the two phases overlap. Smedema et al evaluated the diagnostic role of cardiac MRI in 58 patients with suspected CS and reported that DE showed favorable sensitivity and specificity of 100% and 78%, respectively [42]. Kim et al compared the prognostic value of DE in cardiac MRI with JMHW's criteria in an asymptomatic cohort of 81 patients with biopsy-proven extra-cardiac sarcoidosis [43].…”
Section: Cardiac Mrimentioning
confidence: 99%